SPADA : Output Supporting Media The Urgency of General Courses Citizenship Education Students of Universitas Pendidikan Indonesia - Neng Saina; Lusiana Brilliant Imani (Jurnal Civicus, 2022)
Citizenship Education is a Compulsory General Subject for all students. Online Learning System or SPADA as one of the distance learning media that is applied in the Citizenship Education course at the Indonesian University of Education. Various influences and obstacles to the use of the Online Learning System are experienced by students in understanding learning material in order to achieve the output of Citizenship Education urgency. This study aims to find out how the influence of the Online Learning System has on the urgency output of student Citizenship Education. The research method used is the mixed method, a combination of qualitative and quantitative with observation instruments, literature studies, and questionnaires. The target is all Office Management Education 2020 A students. The results of this study can be concluded that the Online Learning System has been useful and has had an influence of 80% to produce the urgency output of MKWU Citizenship Education for students of the Indonesian University of Education, especially for students of Office Management Education 2020 A. This is supported by various obstacles and strategies in understanding Citizenship Education material in the Online Learning System